Choice of antimuscarinic agents for overactive bladder in the older patient: focus on darifenacin - Bilal Chughtai (Dove Medical Press, 2008)
Bilal Chughtai1, Robert Levin2, Elise De11Albany Medical College, Division of Urology; 2Albany College of Pharmacy and Stratton VAMC, Albany, NY, USAAbstract: Overactive bladder (OAB) is a difficult condition to live with and is very costly tothe community. OAB affects 16% of the adult population and rises with increasing age. We describe the necessary steps in evaluation and behavioral therapy prior to initiating medical therapy. There are several medications that have been used for the treatment of patients who suffer from OAB. This manuscript discusses the popular agents used for OAB, with a focus on the recent clinical trials on darifenacin.Keywords: darifenacin, overactive bladder, urge incontinence, older patients, aging